2013
DOI: 10.1638/2013-0044r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Antemortem Diagnosis and Successful Management of Noncompressive Segmental Myelopathy in a Siberian-Bengal Mixed Breed Tiger

Abstract: A 10-yr-old female spayed mixed breed tiger presented for a 9-day history of acute and nonprogressive paralysis of the pelvic limbs. Magnetic resonance imaging revealed a lesion suggestive of fibrocartilaginous embolic myelopathy with regional spinal cord edema, decreased disk signal intensity at L2-L3, and mild intervertebral disk protrusion at L1-L2 and L2-L3. Cerebral spinal fluid analysis showed no overt evidence of infection or neoplasia. Medical therapy was instituted, including corticosteroids and gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Anatomic location of the disc herniations in these cases varied, affecting the cervical, thoracolumbar, lumbar, and lumbosacral regions, consistent with other reports in large carnivores. 8,9,14,16,17,29 Diagnostic imaging, particularly MRI, was effective at localizing lesions in each case, as has been demonstrated in large felids previously. 12…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Anatomic location of the disc herniations in these cases varied, affecting the cervical, thoracolumbar, lumbar, and lumbosacral regions, consistent with other reports in large carnivores. 8,9,14,16,17,29 Diagnostic imaging, particularly MRI, was effective at localizing lesions in each case, as has been demonstrated in large felids previously. 12…”
Section: Discussionsupporting
confidence: 65%
“…13,21 However, a recent American College of Veterinary Internal Medicine (ACVIM) consensus statement revealed that surgical intervention carried more favorable outcomes in nearly all cases of acute canine thoracolumbar IVDD. 20 IVDD affecting captive large felids has mostly been described in the literature as individual case reports in tigers, 8,9,14,17,18,24 but is a commonly encountered syndrome for zoo practitioners. Anecdotally, the vast majority of IVDD cases in captive Panthera spp.…”
Section: Introductionmentioning
confidence: 99%
“…An ischemic event of a different etiology such as fibrocartilaginous embolism is therefore also considered. Cases of confirmed and suspected fibrocartilaginous embolism have previously been reported in non-domestic felids ( 13 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MRI examination in a tiger with suspected Clostridium perfringens neurotoxicosis did not reveal any abnormalities other than an incidental empty sella ( 12 ). MRI findings in a tiger with noncompressive segmental myelopathy suspected to represent a fibrocartilaginous embolism included regional T2 hyperintensity of the spinal cord and decrease in normal T2 hyperintensity of regional intervertebral discs associated with mild noncompressive intervertebral disc protrusions ( 13 ). Multifocal bone lesions were reported in a tiger ultimately diagnosed with multiple myeloma ( 14 ).…”
Section: Introductionmentioning
confidence: 99%